Impurity ion drift and toroidal rotation in tokamaks - McNeill, D.H. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
This is an analysis of the toroidal drifts of bulk (hydrogenic) and impurity ions, and electrons, in ohmically heated tokamaks. Experimentally observed ion drift is consistently explained by a 1-D model with Ohm's law and the charged particle equations of motion in a quiescent plasma. Calculations show that the drifts are usually decoupled, so the notion of "toroidal rotation" of the plasma as a whole is untenable in this situation.